ANALYSIS THE EFFECT OF SENSORY INTERVENTION ON PATIENT'S ANXIETY ACCORDING TO MAGNETIC RESONANCE IMAGING-ANXIETY QUESTIONNAIRE (MRI-AQ) AND HEART RATE IN MRI LUMBAL EXAMINATION - Andeizi, Tifan Nata; Devianti Putri, Berliana; Muhaimin; Muqmiroh, Lailatul; Setiawati, Rosy (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: The use of MRI as a non-invasive diagnostic radiological examination modality is painless. However, patients may experience claustrophobia and anxiety. Sensory intervention is a method of providing sensory stimulation to an individual, which is expected to reduce the anxiety. Purpose: To determine the effect of the sensory intervention on the anxiety level of patients using an intervention scent by inhalation and intervention sound based on heart rate and MRI-AQ in patients with MRI lumbal examination. Method: 24 samples were divided into three groups: intervention scent, combination intervention scent-sound, and control, with eight samples each. Intervention scent is given using lavender essential oil as aromatherapy, drop three drops on the mask, then put the mask on for 5 minutes before the examination until the examination is completed. Intervention sound is given by playing music (nature-sound) during the examination. Result: Sensory intervention, specifically the use of combination intervention scent-sound, significantly reduces anxiety in patients during MRI lumbal examination significantly p = 0.004 (p<0.05). Conclusion: The use of a combination between lavender and nature-sound as media for sensory intervention has a positive effect on reducing anxiety during MRI lumbal examination based on heart rate. Due to the easy administration of this aromatherapy and the minimal risk for this treatment, it is recommended that it is applied to reduce anxiety during MRI.